(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
This study implemented and evaluated an occupational stress management program for a group of 74 non-academics from a private university in the state of Goiás, Brazil. Forty-two employees attended a multimodal intervention for stress management while the other 32 attended social skills training. Both were conducted in 12 group sessions of 60 minutes each, during working hours. Preand post-test measurements were taken for immunity, blood pressure, and verbal stress responses, social skills and coping with problems at work. Covariance analyses and analyses of variance with stratification has demonstrated that the participants in both interventions presented similar levels of stress symptoms, coping with problems at work, social skills and immunity. They only differed in terms of diastolic blood pressure: The participants from the stress management intervention showed lower mean results (F (3.73) = 15.69, p< .05) for this variable. The results did not indicate that one type of intervention was superior to the other.